2023
DOI: 10.1002/aenm.202301667
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High Thermoelectric Performance in N‐Type Mg3(Sb, Bi)2‐Based Materials via Synergetic Mo Addition and Sb–Bi Ratio Refining

Abstract: Developing thermoelectric (TE) performance is impeded by the compromise of TE parameters, resulting in inadequate conversion efficiency of heat to electricity. Herein, this work reports that Mo is a particularly effective additive in Mg3Sb2‐based alloys with significantly improved electronic transport via grain‐boundary engineering and band‐structure regulation synergy. In addition, phonon transport is simultaneously suppressed by employing multiple effects, lattice imperfection scattering, reduced phonon grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…17 exhibit the contribution from the modified interfacial barrier to S, where the data points deviate upward slightly. Recently, it has been reported that the Mo addition also increases the σ of Mg 3 (Sb,Bi) 2 -based materials 38 , indicating the great potential of other transition metals. However, the enhanced σ by Mo addition is mainly due to the grain boundary effect, different from those analyzed above for the Nb or Ta inclusions.…”
Section: Resultsmentioning
confidence: 99%
“…17 exhibit the contribution from the modified interfacial barrier to S, where the data points deviate upward slightly. Recently, it has been reported that the Mo addition also increases the σ of Mg 3 (Sb,Bi) 2 -based materials 38 , indicating the great potential of other transition metals. However, the enhanced σ by Mo addition is mainly due to the grain boundary effect, different from those analyzed above for the Nb or Ta inclusions.…”
Section: Resultsmentioning
confidence: 99%
“…The figure of merit ZT is defined as ZT = S 2 σT / κ , where S is the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, and κ is the thermal conductivity. 3,4 To produce greater thermoelectric power generation, a large temperature difference (Δ T = T h − T c ) and a high ZT ave are desired. 5 However, the high-performance temperature range of typical TE materials is usually narrow.…”
Section: Introductionmentioning
confidence: 99%
“…Mg 3 Sb 2 -based thermoelectric materials, which consist of earth-abundant elements and are environmentally friendly, show great potential for low temperature power generation. Most recently, it has attracted great attention in the thermoelectric community, and the thermoelectric properties of Mg 3 Sb 2 -based materials have been greatly improved. Liu et al reported that the maximum ZT values above ∼1.6 at 673 K and average ZT above ∼1.0 between 300 and 673 K are attained by Er, Dy, Gd, and Nd doping. These dopants optimize the carrier concentration, increase the density of states effective mass, and suppress the scattering of ionized impurities in Mg 3 Sb 2 -based compounds .…”
Section: Introductionmentioning
confidence: 99%